GRAVITY MODEL DISTRIBUTION MODELLING IN THE CITY OF MUARA TEWEH - Antonius Evendri (Lambung Mangkurat University Press, 2014)
Transportation is a fundamental factor in the life of the nationand state , has the function as a driver, driving and supporting development. The user is the public transport services that require transportation services in conducting both in political, social, economic, cultural as well as in the field of defense - security state . The more years of growth, the higher the number of vehicles in the City of Muara Teweh, hence the need for transportation planning in the city of Muara Teweh to solve transportation problems into the future. Teweh Muara town as a center of activity in the North Barito regency will not be separated from the problem of movement of people, this movement generates patterns of movement of people, therefore it is necessary to study the pattern of movement of people to get a standard formula that can be used in calculating the movement patterns of people in the city of Muara Teweh. The method used is by a factor of Gravity Model barriers of distance , time and distance - time combination . Data movement is obtained by questionnaire spread on junior high school and high school in the city of Muara Teweh by 9 schools with a total of 5125 questionnaires were distributed as kousioner where it produces household data movement. From the results of the household interview survey of 9454 earned a total movement of movements consisting of 16 zones of internal and 4 external zones with a total of 20 zones. MAT observations occurred in zone 3 of 2741 movement and the movement of the smallest occurred in zone 18 by 26 movement . From the results of calculation of MAT Gravity Model which only takes into account the movement of the zone to the market value of   = 1.06 is obtained for the barrier function of distance and time . Statistical test using Chi Square test for distance and time barriers factors, from statistical test results obtained 75% of the samples received by the entire sample of residential and 25% of samples are not received by the sample settlement with the 95% confidence level .By looking at the results of the original and modeling results that meet the 75% level of confidence in the value of   = 1.06 can be used specifically for the calculation of MAT in the city of Muara Teweh whit the Gravity Model.